The Complete Genome and Proteome of Mycoplasma mobile - Jaffe, Jacob D.; Stange-Thomann, Nicole; Smith, Cherylyn; DeCaprio, David; Fisher, Sheila; Butler, Jonathan; Calvo, Sarah; Elkins, Tim; FitzGerald, Michael G.; Hafez, Nabil; Kodira, Chinnappa D.; Major, John; et al. (Genome Research, 2004)
Although often considered “minimal” organisms, mycoplasmas show a wide range of diversity with respect to host environment, phenotypic traits, and pathogenicity. Here we report the complete genomic sequence and proteogenomic map for the piscine mycoplasma Mycoplasma mobile, noted for its robust gliding motility. For the first time, proteomic data are used in the primary annotation of a new genome, providing validation of expression for many of the predicted proteins. Several novel features were discovered including a long repeating unit of DNA of ∼2435 bp present in five complete copies that are shown to code for nearly identical yet uniquely expressed proteins. M. mobile has among the lowest DNA GC contents (24.9%) and most reduced set of tRNAs of any organism yet reported (28). Numerous instances of tandem duplication as well as lateral gene transfer are evident in the genome. The multiple available complete genome sequences for other motile and immotile mycoplasmas enabled us to use comparative genomic and phylogenetic methods to suggest several candidate genes that might be involved in motility. The results of these analyses leave open the possibility that gliding motility might have arisen independently more than once in the mycoplasma lineage.
10.1101/gr.2674004